Feminist Reconstructions Of Christian doctrine Narative Analysis and Appraisal - Greene-McCreight, Kathryn (New York Oxford University Press, 2000)
What is the relationship between feminist theology and classical Christian theology? Is feminist theology "Christian," and if so, in what respect and to what extent? This study seeks to analyze and evaluate the relation of feminist "reconstructions" to tr
Keywords: Feminist theology. RELIGION -- Christianity -- General. RELIGION -- Christian Theology -- Systematic. Feministische theologie. Systematische theologie